2005
DOI: 10.1063/1.2150280
|View full text |Cite
|
Sign up to set email alerts
|

Chemical functionalization of GaN and AlN surfaces

Abstract: The covalent functionalization of GaN and AlN surfaces with organosilanes is demonstrated. Both octadecyltrimethoxysilane and aminopropyltriethoxysilane form self-assembled monolayers on hydroxylated GaN and AlN surfaces, confirmed by x-ray photoelectron spectroscopy and atomic force microscopy. The monolayer thickness on GaN was determined to 2.5± 0.2 nm by x-ray reflectivity. Temperature-programmed desorption measurements reveal a desorption enthalpy of 240 kJ/ mol. The application of these devices for elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 21 publications
3
87
0
1
Order By: Relevance
“…8 The oxidized AlInN/GaN heterostructures could also be used for chemical sensing devices, similar to the other III-nitrides and their compounds. [9][10][11][12][13][14] An interesting aspect related to this application field might be a low density of stress-induced defects expected for the lattice-matched heterostructures. This particular characteristic could possibly improve the stability of AlInN surface against corrosion in electrolytes, as it is well known that the chemical limits of III-nitrides depend very much on their crystalline quality.…”
Section: Introductionmentioning
confidence: 99%
“…8 The oxidized AlInN/GaN heterostructures could also be used for chemical sensing devices, similar to the other III-nitrides and their compounds. [9][10][11][12][13][14] An interesting aspect related to this application field might be a low density of stress-induced defects expected for the lattice-matched heterostructures. This particular characteristic could possibly improve the stability of AlInN surface against corrosion in electrolytes, as it is well known that the chemical limits of III-nitrides depend very much on their crystalline quality.…”
Section: Introductionmentioning
confidence: 99%
“…Alkylsilane SAMs have also been formed on many other substrates like H-terminated silicon [162], silicon nitride [163], aluminum oxide [164,165], aluminum alloy [166], tantalum pentoxide [167], coppper [168], titanium [154], titania [154], quartz [169][170][171], glass [172], mica [173,174], zinc selenide [164,172], nickel [154], chromium [154], iron [154], steel [175],carbon [176], niobium [154], zirconium [154], zirconium dioxide [151], hafnium dioxide [151], germanium oxide [172], indium tin oxide (ITO) [177], gallium nitride [178], gold [179,180], cobalt chromium [181], etc. Bradshaw et al have carried out chemisorption studies of methylsilane on nickel, rhodium, tungsten and molybdenum [154,182,183].…”
Section: Silane Nanocoatings/silane Self Assembled Monolayers (Sams)mentioning
confidence: 99%
“…In several studies, APTES monolayers have been reported, including those on GaN [37], silicon oxide [38], and porous silicon [39]. However, it is difficult to distinguish a monolayer from dispersed molecules of APTES deposited in a limited time [40,41].…”
Section: Deposition Of Aminosilane On the Diamond Surfacementioning
confidence: 99%